PHENOTYPIC SCREENING OF THE BREEDING LINES OF MTU 1010 DERIVED THROUGH MARKER-ASSISTED PEDIGREE BREEDING FOR RESISTANCE AGAINST BACTERIAL BLIGHT AND BLAST - R. M. SUNDARAM, B. LAXMI PRASANNA, KULDEEP SINGH DANGI, CH. DAMODAR RAJU, R. JAGADEESHWAR and (The Journal of Research, PJTSAU, 2019)
In the present study, two major genes, viz., Xa21 and Pi54 conferring resistance against bacterial blight (BB) and blast, respectively were transferred into an Indian rice variety MTU1010. NILs of Akshyadhan (RP6132) possessing Xa21 and Pi54 was used to transfer the target traits into NIL of MTU1010 (RP5973-20-9-8-24-12-7), which is highly susceptible to both BB and blast diseases, but tolerant to low soil P. A marker-assisted pedigree breeding approach was adopted to combine low soil phosphorous tolerance, Xa21 and Pi54. Plants at F3 generation were observed to be highly resistant against bacterial blight and blast along with high yield, good agronomic attributes and low shattering of grains, which is a major problem in MTU1010. This work demonstrates the successful application of marker-assisted breeding for combining BB and blast genes (Xa21 + Pi54) into a low P tolerant NIL of MTU1010 (RP 5973-20-9-8-24-12-7). All the 15 F3 lines were also observed to be resistant to bacterial blight and blast through phenotypic screening and possessed grain yields and grain quality equivalent to or better than the MTU1010 NIL. Two breeding lines viz., LPK 30-18-16 and LPK 49-15-22 respectively, exhibited good performance with high level of resistance to all the three stresses viz., BB, blast and low soil P and possessed high yield under both normal soil P and low soil P with highly desirable long slender grain type like MTU1010.